Rita Levi-Montalcini: the neurologist who challenged fascism - Léo Coutinho; Hélio A. Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
Rita Levi-Montalcini was a researcher in the field of neuroscience, Italian and Jewish in origin, who discovered the nerve growth factor and rightfully earned the 1986 Nobel Prize in Physiology or Medicine, alongside her collaborator Stanley Cohen. She was persecuted by the fascist dictatorship of Benito Mussolini and experienced gender and religious discrimination throughout her entire life. Despite these obstacles, she carried out her activities with diligence and grace, becoming a role model in the field. This paper reviews the life and career of Rita Levi-Montalcini.